-2z-7y=7+7

Simple and best practice solution for -2z-7y=7+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2z-7y=7+7 equation:


Simplifying
-2z + -7y = 7 + 7

Reorder the terms:
-7y + -2z = 7 + 7

Combine like terms: 7 + 7 = 14
-7y + -2z = 14

Solving
-7y + -2z = 14

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2z' to each side of the equation.
-7y + -2z + 2z = 14 + 2z

Combine like terms: -2z + 2z = 0
-7y + 0 = 14 + 2z
-7y = 14 + 2z

Divide each side by '-7'.
y = -2 + -0.2857142857z

Simplifying
y = -2 + -0.2857142857z

See similar equations:

| 4x-12x+3=5 | | x-2(-2x+5)=2 | | 12x+22=-9x-41 | | -144=-8x | | 3n-8=32n | | x=ky+f | | 6x-99=-5x | | 4(x-1)+3(x+1)= | | 217.25=3 | | 4x-(2x+5)=3x-10 | | 6m-6=6m+18 | | 2x+3x+3=-12 | | 21p-62=38+p | | 8x+12-2x-5=3 | | y=kx+f | | 2(2+5x)=9(x-1) | | 81c^2+18c+1= | | 9[5-7(x-1)]+6[(5x+7)-8]=11x-336 | | (1-5j)+(-2-6j)=-1-11j | | 6x+x^2=84 | | 9c^2-8c-1= | | 4-x=4x+19 | | -3(x+3)=5x | | 0.004(2-k)+0.09(k-7)=1 | | 1x+4x=43 | | 13-4x+12=13 | | 4t-3=37-t | | 5b-7=-13 | | 5x+22+2x=-48 | | x-7/6=1-x/7 | | 5g+7+3g=31 | | 60a^5-24a^4+36a^3= |

Equations solver categories